Lillias Hamilton: Personal physician to the Amir of Afghanistan. (November 2021) - Timmis, Christopher
Lillias Hamilton trained as a doctor in London, qualified in 1890 and practiced in Calcutta and later in Afghanistan where she was the personal physician to the Amir and the only Western doctor. After six years abroad, she returned to England but owing partly to establishment prejudice was unsuccessful in setting up a London practice and eventually became the Principal of a Women's Agricultural College. Her career illustrates the aspects of medical practice abroad in the 1890s, as well as the difficulties encountered by women doctors in England even after the route to qualification in the UK had been opened.